2018
DOI: 10.1016/j.jobe.2018.01.010
|View full text |Cite
|
Sign up to set email alerts
|

Building life cycle applied to refurbishment of a traditional building from Oporto, Portugal

Abstract: Buildings management along with its life cycle is currently an issue that requires a great optimisation considering the high cost associated with the buildings use and due to the operation and maintenance costs. The number of existing buildings needing refurbishment actions justify the need of an intervention model that optimise its service life after the refurbishment process. So, a refurbishment, maintenance and costs planning should be established and guided by value for money principles. The aim of this pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(15 citation statements)
references
References 12 publications
0
14
0
Order By: Relevance
“…The aim of the first step was to define the scope of the literature review. BIM is an interdisciplinary digital tool that has been studied in various AEC areas, such as: project management (Cao et al , 2018), construction automation (Mangal and Cheng, 2018), building performance analysis (Pinheiro et al , 2018), structural analysis (Ramaji and Memari, 2018), facility management (Rodrigues et al , 2018), as well as BIM integrated with other emerging technologies such as laser scanning (Santos et al , 2017). This study was about BIM-based research that focused on CEM activities, tasks, processes, issues, or human factors such as construction planning and constructability evaluation (Nascimento et al , 2017).…”
Section: Methodsmentioning
confidence: 99%
“…The aim of the first step was to define the scope of the literature review. BIM is an interdisciplinary digital tool that has been studied in various AEC areas, such as: project management (Cao et al , 2018), construction automation (Mangal and Cheng, 2018), building performance analysis (Pinheiro et al , 2018), structural analysis (Ramaji and Memari, 2018), facility management (Rodrigues et al , 2018), as well as BIM integrated with other emerging technologies such as laser scanning (Santos et al , 2017). This study was about BIM-based research that focused on CEM activities, tasks, processes, issues, or human factors such as construction planning and constructability evaluation (Nascimento et al , 2017).…”
Section: Methodsmentioning
confidence: 99%
“…Much research has been done recently on how to reduce the environmental impacts of the existing building stock with refurbishment measures (Häkkinen 2012;Ballarini et al 2014;Assiego de Larriva et al 2014;Oregi et al 2015Oregi et al , 2017Corrado and Ballarini 2016;Agostino et al 2017). These studies mainly focus on investigating different refurbishment approaches and their influence on the environmental impacts of the buildings (Stazi et al 2012;Pomponi et al 2015;Ortiz et al 2016;Passer et al 2016;Ruud et al 2016;Rodrigues et al 2018). For the calculation of the environmental impacts the life cycle asessment (LCA) methodology is often applied.…”
mentioning
confidence: 99%
“…The context of existing and future residential structures for hydro-thermal modelling and monitoring tools was another subject for health monitoring [ 244 ]. The advantages of utilization BIM for monitoring and optimization of complex refurbishment cases were the main subject of various studies that investigated the barriers and research directions of this approach [ 121 , 245 , 246 , 247 , 248 , 249 ]. Okakpu et al [ 250 ] identified four dimensions that encompassed the impacts of BIM adoption specific to refurbishment projects and Becker et al [ 248 ] conducted research for data collection and actual modelling.…”
Section: Content Analysismentioning
confidence: 99%
“…The future work in this category includes considering the inherent value of confined space monitoring system (CoSMoS), advanced methods for achieving patterns in real-time data for creating an intelligent digital built environment [ 243 ], BIM effects on application of life cycle assessment in buildings refurbishment [ 249 ] and development of intra-data collection to monitor local projects [ 251 ].…”
Section: Content Analysismentioning
confidence: 99%